Thirty-fifth anniversary of the International Journal of Hospitality Management: A bibliometric overview. (April 2019) - Martorell Cunill, Onofre; Socias Salvá, Antonio; Otero Gonzalez, Luis; Mulet-Forteza, Carles
Highlights: The most productive and influential institutions in IJHM. A dynamic analysis of the publications in IJHM. A graphical visualization by using the VOS viewer software. An overview useful for researchers and institutions in their decision-making. The hot topic research in IJHM. Abstract: International Journal of Hospitality Management is a leading journal in 'Hospitality, Tourism and Management' field. The journal celebrated its 35th anniversary in 2016. The aim of this paper is to provide a complete lifetime overview of the academic structure of the journal using bibliometric indicators since its inception and until the last year completed. This analysis includes key factors such as the most cited articles, leading authors, originating institutions and countries, the publication and citation structures, and the keywords most commonly used. The bibliometric data used to conduct this analysis come from the Scopus database. Additionally, the VOS viewer software is used to create a graphic map of the bibliometric results. The graphical analysis uses co-citation, bibliographic coupling and co-occurrence. Results indicate that IJHM is a leading journal in the areas where it is indexed, with publications from a wide range of authors, institutions, and countries around the world.